DNA methylation classifier to diagnose pancreatic ductal adenocarcinoma metastases from different anatomical sites - Calina, Teodor G.; Perez, Eilís; Grafenhorst, Elena; Benhamida, Jamal; Schallenberg, Simon; Popescu, Adrian; Koch, Ines; Janik, Tobias; Chen, BaoQing; Ihlow, Jana; Rössler, Stephanie; Goeppert, Benjamin; et al. (Clinical epigenetics, 2024)
We have recently constructed a DNA methylation classifier that can discriminate between pancreatic ductal adenocarcinoma (PAAD) liver metastasis and intrahepatic cholangiocarcinoma (iCCA) with high accuracy (PAAD-iCCA-Classifier). PAAD is one of the leading causes of cancer of unknown primary and diagnosis is based on exclusion of other malignancies. Therefore, our focus was to investigate whether the PAAD-iCCA-Classifier can be used to diagnose PAAD metastases from other sites.
Online veröffentlicht: 10. November 2024
Gesehen am 20.08.2025